(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The opalites and qwarzites of newly discovered mine-deposite of Gomshategh are the most famous ones- due to the rich content of silicate rocks and silicium-oxide, free of elementary mixtures. On the bases of new technological schemes, the specialists of The Institute of Common and Disorganic Chemistry of The National Academy of Sciences of Armenia found out, that the opalites are being represented as a unique base material for production of ceramic, electronical-optical equipment, and especially for production of artificial vollastonite, sodium-hydrosilicate, several metallic silicates and a highly pure silicium-oxide for production of optical and electronical-vacuum glass. The opalites became a new type of nonmetallic deposite-material due to new technologies that revealed new spheres of their practical use in science and engineering.